Ruthenium-catalyzed C6-propenylation reactions of substituted pyridine derivatives: directed and direct C-H activation - Goriya, Yogesh; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
Keywords: alkenylation; C?H activation; nitrogen heterocycles; pyridine derivatives; ruthenium

Ru-catalyzed branched versus linear selective C3-alkylation of 2-aroylbenzofurans with acrylates via C-H activation - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, Chepuri V. (Chemistry-A European Journal, 2014)
The carbonyl-directed C3-H activation and alkylation of 2-aroylbenzo[b]furans with acrylates occurs selectively either in a linear or branched fashion, depending on the catalyst employed; [Ru(p-cymene)Cl-2](2) or Ru(PPh3)(3)Cl-2, respectively. Two alternate pathways-funded upon the differences in steric and electronic preferences of these two complexes-is proposed for the selectivity of linear versus branched products.
Keywords: acrylate; benzo[b]furan; branched-selective alkylation; C-H activation; ruthenium

Ru-catalyzed redox-neutral cleavage of the N-O bond in isoxazolidines: isatogens to pseudoindoxyls via a one-pot [3+2]-cycloaddition/N-O cleavage - Kumar, Chepuri V. Suneel; Ramana, Chepuri V. (Organic Letters, 2015)
A novel metal-catalyzed oxygen atom transfer reaction onto olefins is reported. By taking isatogens as substrates, a one-pot [3 + 2]-cycloaddition of nitrone with olefins followed by the Ru-catalyzed redox-neutral N-O bond cleavage of intermediate isoxazolidine has been executed as a simple method for the synthesis of 2,2-disubstituted pseudoindoxyls.

Ruthenium(II)-catalyzed C3 arylation of 2-aroylbenzofurans with arylboronic acids/aryltrifluoroborates via carbonyl-directed C-H bond activation - Paymode, Dinesh J.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2015)
The Ru(II)-catalyzed carbonyl-directed C-H activation with (hetero)arylboron reagents has been executed for the synthesis of 2-aroyl-3-(hetero)arylbenzofurans. A hypothesis founded upon the involvement Of an active carbonatoruthenium(II) complex for a coordinative insertion and the aerobic oxidation of the in situ generated Ru(0) to Ru(II), to continue the catalytic cycle, has been extended.

Ruthenium(II)-catalyzed switchable C3-alkylation versus alkenylation with acrylates of 2-pyridylbenzofurans via C-H bond activation - Kommagalla, Yadagiri; Mullapudi, Venkanna Babu; Francis, Fredi; Ramana, Chepuri V. (Catalysis Science & Technology, 2015)
We documented an interesting observation of ruthenium (II)-catalyzed benzofuran C-H activation and subsequent functionalization with acrylates that reveals that a simple base can switch the process from alkylation to alkenylation.

Re-engineering of PIP3-antagonist triazole PITENIN's chemical scaffold: development of novel antifungal leads - Pulya, Sravani; Kommagalla, Yadagiri; Sant, Duhita G.; Jorwekar, Shweta U.; Tupe, Santosh G.; Deshpande, Mukund V.; Ramana, Chepuri V. (RSC Advances, 2016)
A novel 4-(1-phenyl-1-hydroxyethyl)-1-(o-hydroxyphenyl)-1H-1,2,3-triazole was designed by integrating the structural features of triazole PITENIN anticancer agents and the azole class of antifungal drugs. A two-step protocol comprising the Barbier propargylation and Cu-catalyzed azide-alkyne cycloaddition was established to synthesise a diverse set of compounds of this class. Their screening against a wide range of human fungal pathogens led to identification of several potential antifungal hits and some of them displayed better antifungal activity than fluconazole against Candida glabrata, Cryptococcus neoformans, Aspergillus fumigatus and Aspergillus niger. Mode of action studies revealed that their antifungal activity was resulting either from the inhibition of lanosterol 14 alpha-demethylase enzyme (leading to ergosterol depletion) or by the generation of reactive oxygen species (ROS).

Ru(II)-catalyzed C-H activation/alkylation of 3-formylbenzofurans with conjugated olefins: product divergence - Srinivas, Kolluru; Siddiqui, Shaziyaparveen K.; Mudaliar, Jyothi K.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
Ru-catalyzed alkylation of 3-formylbenzofuran with acrylates and acrylamides has been described. Branched selectivity with unsubstituted or beta-substituted acrylates/ acrylamides and linear selectivity with alpha-substituted acrylates have been observed. However, in all of the cases, the intermediate alkylation products seem to undergo further reactions, either cycloannulation or deformylation, depending on the substrate employed. For example, with methyl acrylate, the intermediate branched alkylation product underwent cycloannulation with another molecule of methyl acrylate, resulting in a densely functionalized cyclohexene ring formation. On the other hand, in the case of N-monosubstituted acrylamides, the branched alkylation proceeded with intramolecular aldehyde-amide condensation, leading to pyridin-2-one ring annulation. However, with both methacrylate and crotonate, deformylation of the initially formed alkylation products was observed.

Rh-catalyzed C-H functionalization of the (Pyrazol-5-yl)pyridine core of GBT-440 - Kalshetti, Rupali G.; Halnor, Swapnil V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2023)
The Rh-catalyzed cross dehydrogenative coupling (CDC)/alkylation of the pyrazolylpyridine unit of GBT-440 proceeded smoothly under ambient conditions and selectively on the pyrazole unit while directed by the pyridine. The scope of these reactions was established by employing simple as well as conjugated olefins for CDC and various diazo esters and the TIPS-EBX reagent for alkylation. At the outset, a focused small molecule library around the bis-heterocyclic core of GBT440 was developed via C-H functionalization.
Keywords: C-H activation; cross dehydrogenative coupling; diazo ester; GBT-440; Rh catalysis; TIPS-EBX